Multifunctional antibiotic- and zinc-containing mesoporous bioactive glass scaffolds to fight bone infection. (15th September 2020) - Heras, C.; Jiménez-Holguín, J.; Doadrio, A.L.; Vallet-Regí, M.; Sánchez-Salcedo, S.; Salinas, A.J.
Abstract: Bone regeneration is a clinical challenge which requires multiple approaches. Sometimes, it also includes the development of osteogenic and antibacterial biomaterials to treat the emergence of possible infection processes arising from surgery. This study evaluates the antibacterial properties of gelatin-coated meso-macroporous scaffolds based on the bioactive glass 80%SiO2 –15%CaO–5%P2 O5 (mol-%) before (BL-GE) and after being doped with 4% of ZnO (4ZN-GE) and loaded with both saturated and the minimal inhibitory concentrations of one of the antibiotics: levofloxacin (LEVO), vancomycin (VANCO), rifampicin (RIFAM) or gentamicin (GENTA). After physical-chemical characterization of materials, release studies of inorganic ions and antibiotics from the scaffolds were carried out. Moreover, molecular modelling allowed determining the electrostatic potential density maps and the hydrogen bonds of antibiotics and the glass matrix. Antibacterial in vitro studies (in planktonic, inhibition halos and biofilm destruction) with S. aureus and E. coli as bacteria models showed a synergistic effect of zinc ions and antibiotics. The effect was especially noticeable in planktonic cultures of S. aureus with 4ZN-GE scaffolds loaded with VANCO, LEVO or RIFAM and in E. coli cultures with LEVO or GENTA. Moreover, S. aureus biofilms were completely destroyed by 4ZN-GE scaffolds loaded with VANCO, LEVO or RIFAM and the E. coli biofilm total destruction was accomplished with 4ZN-GE scaffolds loaded with GENTA or LEVO. This approach could be an important step in the fight against microbial resistance and provide needed options for bone infection treatment. Statement of Significance: Antibacterial capabilities of scaffolds based on mesoporous bioactive glasses before and after adding a 4% ZnO and loading with saturated and minimal inhibitory concentrations of levofloxacin, vancomycin, gentamicin or rifampicin were evaluated. Staphylococcus aureus and Escherichia coli were the infection model strains for the performed assays of inhibition zone, planktonic growth and biofilm. Good inhibition results and a synergistic effect of zinc ions released from scaffolds and antibiotics were observed. Thus, the amount of antibiotic required to inhibit the bacterial planktonic growth was substantially reduced with the ZnO inclusion in the scaffold. This study shows that the ZnO-MBG osteogenic scaffolds are multifunctional tools in bone tissue engineering because they are able to fight bacterial infections with lower antibiotic dosage. Graphical abstract: Image, graphical abstract